Highly solid-luminescent graphitic C3N4 nanotubes for white light-emitting diodes. (3rd October 2019) - Zheng, Xuegang; Cui, Guangliang; Yang, Siwei; Zhang, Shouyan; Yuan, Xuanhao; Li, Jianfu; Zhang, Pinhua; Ding, Guqiao; Wang, Hailong
Abstract: Graphitic C3 N4 (g-C3 N4 ) has seldom been used for white light-emitting diode (LED) phosphors due to its low solid-state fluorescence quantum yield. Here, we report a facile thermal condensation path for the synthesis of g-C3 N4 nanotubes stuffed with quantum dots. The g-C3 N4 nanotubes have a high fluorescence quantum yield of 30.92% in the solid state. Nitrogen-rich and graphitic carbon-free features are responsible for the enhanced quantum efficiency. The photoluminescence quantum yield can be controlled and improved by the reaction temperature. We finally demonstrate white light emission by coating the highly solid-luminescent g-C3 N4 nanotubes as phosphors onto a 370 nm ultraviolet LED.